PENGARUH LAYANAN KONSELING KELOMPOK UNTUK MENGURANGI PERILAKU BULLYING PADA SISWA KELAS VII SMPN 1 TERARA LOMBOK TIMUR - Mahyatun, Baiq; Ariska, Desi (JKP (Jurnal Konseling Pendidikan), 2024)
Bullying is a very long-term physical and psychological abuse carried out by one person or a group of people, targeting individuals who have no physical defense. In situations like this, the individual who is the victim is made to feel afraid. If bullying is not handled immediately it will be detrimental to both parties. The purpose of this research is to determine the effect of group guidance services to reduce bullying behavior in class VII students at SMPN 1 Terara, East Lombok. This type of research is a quantitative experiment using a one-group pretest and posttest research design involving class VII students at SMPN 1 Terara, East Lombok. The population of this research was class VII students at SMPN 1 Terara, East Lombok. Then a sample of 10 students was obtained using group guidance services to handle these students' problems. The method applied to collect data in this research used questionnaires and observation. The results of this research with a significance value of 0.000 <0.005 can be concluded that group counseling services are effective in reducing bullying behavior in class VII students at SMPN 1 Terara, East Lombok. Keywords: Group Counseling Services, Student Bullying Behavior.